2019
DOI: 10.1080/20008198.2019.1577092
|View full text |Cite
|
Sign up to set email alerts
|

A multisite randomized controlled trial of Seeking Safety vs. Relapse Prevention Training for women with co-occurring posttraumatic stress disorder and substance use disorders

Abstract: Background : Co-occurring posttraumatic stress disorder (PTSD) and substance use disorders (SUD) are associated with a more severe course and worse outcome than either disorder alone. In Europe, few treatments have been evaluated for PTSD and SUD. Seeking Safety, a manualized, integrated, cognitive-behavioural treatment, has been shown to be effective in studies in the USA. Objective : To test the efficacy of Seeking Safety plus treatment as usual (TAU) in female outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 55 publications
0
41
0
1
Order By: Relevance
“…Seeking Safety (Najavits, 2002) is a present‐focused integrated PTSD/SUD treatment that emphasizes establishing safety and coping skills as the primary clinical need for individuals with this comorbidity. Studies have shown that SS is comparable to SUD treatments such as relapse prevention or health education in reducing PTSD and SUD symptoms (Boden et al., 2012; Hien et al., 2009; Schäfer et al., 2019). The results of one direct comparison demonstrated that both COPE and SS reduced PTSD symptoms, with COPE showing larger reductions in PTSD compared to SS (Norman et al., 2019).…”
mentioning
confidence: 99%
“…Seeking Safety (Najavits, 2002) is a present‐focused integrated PTSD/SUD treatment that emphasizes establishing safety and coping skills as the primary clinical need for individuals with this comorbidity. Studies have shown that SS is comparable to SUD treatments such as relapse prevention or health education in reducing PTSD and SUD symptoms (Boden et al., 2012; Hien et al., 2009; Schäfer et al., 2019). The results of one direct comparison demonstrated that both COPE and SS reduced PTSD symptoms, with COPE showing larger reductions in PTSD compared to SS (Norman et al., 2019).…”
mentioning
confidence: 99%
“…Accurate assessments of these mothers should be developed and tailored interventions according to the trauma-informed care perspective should be provided (Covington, 2008). There is a large literature on posttraumatic stress disorder (PTSD) and substance use in women (Melchior et al , 2019), and treatments like Seeking Safety have been developed as a specific and integrated psychotherapy for PTSD and substance use disorder, showing promising results (Lenz et al , 2016; Schaefer et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The data of this study are derived from the baseline data of a larger intervention trial among patients with SUD and PTSD (27) (DRKS00004288).…”
Section: Methodsmentioning
confidence: 99%